ADAM28 as a Target for Human Cancers - Mochizuki, Satsuki; Okada, Yasunori (Current Pharmaceutical Design, 2009)
ADAM28 is a member of the ADAM (a disintegrin and metalloproteinase) gene family and consists of two isoforms, prototype membrane-type form and short secreted form. The metalloproteinase domain of ADAM28 has the zincbinding consensus sequence, andADAM28 exhibits catalytic activity to a few substrates such as insulin-like growth factor binding protein-3. The disintegrin domain interacts with integrins α4β1, α4β7 and α9β1. In human non-small cell lung carcinomas and breast carcinomas, ADAM28 is overexpressed predominantly by carcinoma cells, and the expression correlates with carcinoma cell proliferation and lymph node metastasis. In this review we present our data on the activation of proADAM28, the tissue localization in human cancers and the interaction molecules, and discuss the regulation of ADAM28 activity and gene expression, the functions of ADAM28 in human cancers and the possibility of ADAM28 as a target for cancers.
Keywords: invasion